2008
DOI: 10.1186/1477-3155-6-3
|View full text |Cite
|
Sign up to set email alerts
|

A micro-fluidic study of whole blood behaviour on PMMA topographical nanostructures

Abstract: BackgroundPolymers are attractive materials for both biomedical engineering and cardiovascular applications. Although nano-topography has been found to influence cell behaviour, no established method exists to understand and evaluate the effects of nano-topography on polymer-blood interaction.ResultsWe optimized a micro-fluidic set-up to study the interaction of whole blood with nano-structured polymer surfaces under flow conditions. Micro-fluidic chips were coated with polymethylmethacrylate films and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Our findings with electrospun fibers thus agree with conclusion derived from utilizing other types of surface topographies: it has been widely observed that platelet adhesion and blood reaction both depend on surface roughness [48][49][50][51][52], and that platelet adhesion and blood activation are also affected by other defined surface topographies, i.e. pillars [53], lenses [54] and struts [55].…”
Section: Discussionsupporting
confidence: 81%
“…Our findings with electrospun fibers thus agree with conclusion derived from utilizing other types of surface topographies: it has been widely observed that platelet adhesion and blood reaction both depend on surface roughness [48][49][50][51][52], and that platelet adhesion and blood activation are also affected by other defined surface topographies, i.e. pillars [53], lenses [54] and struts [55].…”
Section: Discussionsupporting
confidence: 81%
“…[2] The rationale for anticoagulation is to prevent thrombus formation on the foreign body until the it endothelizes. [8] The optimal duration of treatment has not been defined. One case report presented evidence of thrombus attached to bone cement retrieved from the right atrium nearly five years post vertebroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…It is the latter three points that have been lacking in previous microfluidic vascular platforms. Most works have focused on a single channel or small (up to 6) arrays that require manual tubing-to-chip connections (Gutierrez et al, 2008;Ku et al, 2008;Maloney et al, 2010;Minelli et al, 2008;Okorie and Diamond, 2006;Sarvepalli et al, 2009). Additionally, because the working lifespan of a fresh blood draw is often short (minutes to hours depending on the type of anti-coagulant treatment used), any optimized device would allow for a large number of samples to be queried quickly and preferably simultaneously with minimal device preparation (Dong, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several microfluidic designs systems have been used to investigate various conditions of matrix deposition, shear flow, and online agonist addition (Gutierrez et al, 2008;Ku et al, 2008;Lincoln et al, 2010;Maloney et al, 2010;Minelli et al, 2008;Okorie and Diamond, 2006;Sarvepalli et al, 2009). Advantages of microfluidic systems for vascular studies include low reagent consumption (especially important for murine and pediatric samples, where sample volumes are limited), physiologically relevant channel dimensions, the promise of quick sample-to-result, accurate flow control, easy fluidics interfacing, and the opportunity for highly parallel studies.…”
Section: Introductionmentioning
confidence: 99%